E-Cigarettes and Cardiovascular Risk: Beyond Science and Mysticism - Lippi, Giuseppe; Favaloro, Emmanuel J.; Meschi, Tiziana; Mattiuzzi, Camilla; Borghi, Loris; Cervellin, Gianfranco (Seminars in Thrombosis and Hemostasis, 2014)
Cigarette smoking is the most important cause of premature death, and it is currently listed as a major independent risk factor for cardiovascular disease. Because of restrictive measures and widespread control policies, tobacco companies are now using aggressive marketing strategies in favor of smokeless tobacco, including electronic nicotine delivery systems, which are also known as electronic cigarettes or e-cigarettes. Although the regular use of these devices appears less hazardous than traditional cigarettes or other forms of smokeless tobacco, recent studies have shown that various potentially harmful substances, especially nicotine, ultraparticles, and volatile organic compounds, may be effectively inhaled or liberated in exhaled air during repeated e-cigarette puffing. This would enhance the risk of cardiac arrhythmias and hypertension, which may predispose some users to increased risk of cardiovascular events, which may be further magnified by other potential adverse effects such as arrhythmias, increased respiratory, and flow respiratory resistance. Some cases of intoxication have also been described, wherein large amounts of nicotine and other harmful compounds may be effectively absorbed. As the use of e-cigarettes is continuously rising, and it is also considered a potentially effective method for smoking cessation, more focused research is urgently needed to definitely establish the cardiovascular safeness of these devices.
Keywords: e-cigarette; electronic cigarette; cardiovascular disease; risk factor; tobacco